Using Technology to Deliver Mental Health Services to Children and Youth: A Scoping Review - Boydell, Katherine M. (Canadian Academy of Child and Adolescent Psychiatry, 2014)
OBJECTIVE: To conduct a scoping review on the use of technology to deliver mental health services to children and youth in order to identify the breadth of peer-reviewed literature, summarize findings and identify gaps. METHOD: A literature database search identified 126 original studies meeting criteria for review. Descriptive numerical summary and thematic analyses were conducted. Two reviewers independently extracted data. RESULTS: Studies were characterized by diverse technologies including videoconferencing, telephone and mobile phone applications and Internet-based applications such as email, web sites and CD-ROMs. CONCLUSION: The use of technologies plays a major role in the delivery of mental health services and supports to children and youth in providing prevention, assessment, diagnosis, counseling and treatment programs. Strategies are growing exponentially on a global basis, thus it is critical to study the impact of these technologies on child and youth mental health service delivery. An in-depth review and synthesis of the quality of findings of studies on effectiveness of the use of technologies in service delivery are also warranted. A full systematic review would provide that opportunity.